2020
DOI: 10.1007/978-3-030-48126-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Fracture Audit

Abstract: Fragility fracture audit is key to understanding fragility fracture management, identifying areas for its improvement and measuring the impact of clinical initiatives and service change. Hip fracture can be considered a marker for fragility fractures, and hip fracture audits indirectly show strengths and weaknesses of fragility fracture care overall. Notably, where effective hip fracture care exists, this has a favourable impact on the care of other fragility fractures. Early established audits, clinically led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…It has been included in a core outcome set for orthogeriatric management of hip fractures and is collected as an outcome in several European hip fracture audits [11,24]. A small minority of Irish studies collected quality of life, and none used the EQ-5D measure that is recommended by the hip fracture core outcome set and integrated into several hip fracture audits internationally [8,10]. This is an important finding as quality of life has been suggested as an outcome that could capture what is important to patients [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been included in a core outcome set for orthogeriatric management of hip fractures and is collected as an outcome in several European hip fracture audits [11,24]. A small minority of Irish studies collected quality of life, and none used the EQ-5D measure that is recommended by the hip fracture core outcome set and integrated into several hip fracture audits internationally [8,10]. This is an important finding as quality of life has been suggested as an outcome that could capture what is important to patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes have been informed by a systematically developed core outcome set for hip fracture trials, which additionally includes quality of life using the EQ-5D patient reported outcome measure (PROM) [8]. National hip fracture audits in Norway, the UK, Germany, Australia, and New Zealand have adopted the EQ-5D at 120 days, although completeness of data has been an ongoing challenge [9,10]. A Core Outcome Set for orthogeriatric management also advocates outcome assessment at 1 year after hip fracture, and 1-year mortality is a commonly assessed outcome in much prognostic research [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis will become an epidemic in the developed world with geriatric hip fractures estimated to increase, particularly in the Asia–Pacific region [ 1 ]. Whilst guidelines encourage early mobilization ubiquitously, the Australian & New Zealand Hip Fracture Registry (ANZFHR) is one of only a few registries to capture unrestricted or full weight-bearing (FWB) as a data field [ 2 ]. Improving mobility in hip fracture is difficult [ 3 ], but consensus is that FWB can facilitate this.…”
Section: Introductionmentioning
confidence: 99%
“…One proven strategy is the ongoing systematic monitoring of hip fracture treatment and patient experience. Ojeda-Thies et al [12] describe this as a fragility fracture audit (others use the term "registry"), with ongoing feedback designed to deliver continuous quality improvement information. Organizations first ascertain the nature of the care they provide, including deficits, by collecting these data.…”
mentioning
confidence: 99%